Nutritional status, age and gender factors associated on pneumonia in congenital heart disease: A hospital-based cross-sectional study in Banda Aceh, Indonesia - Nora Sovira; Herlina Dimiati; Sulaiman Yusuf; Bakhtiar Bakhtiar; Jufitriani Ismy (AcTion: Aceh Nutrition Journal, 2025)
Pneumonia is a leading cause of morbidity and mortality in children with congenital heart disease (CHD). Risk factors for pneumonia in these children include anemia, hypoxemia, nutritional status, congestive heart failure, and neuromuscular disorders. This study aimed to determine the risk factors for pneumonia in children with CHD at the Dr. Zainoel Abidin Public Hospital, Banda Aceh, Indonesia. This analytical, observational study employed a cross-sectional approach. This study included children aged 1 month to 18 years who were treated at the Dr. Zainoel Abidin Public Hospital from January 2022 to December 2023. Data were collected from medical records of 121 children who met the inclusion and exclusion criteria. Data were analyzed using bivariate analysis with the chi-square test and multivariate analysis with logistic regression. Pneumonia was observed in 66 (54,5%) patients. The majority of children with critical illnesses who developed pneumonia were between 1 month and 5 years of age (60%), female (61,7%), had poor nutritional status (53,2%), and had a birth weight ≥ 2500 g (54,5%). The type of CHD was found to be a significant risk factor for pneumonia (p = 0,024), with an odds ratio of 3,16 (95% CI: 1,162–8,617). In conclusion, the CHD type is a risk factor for pneumonia in children with CHD.